The making of Persianate modernity : language and literary history between Iran and India - Jabbari, Alexander (Cambridge ; New York, NY ; India : Cambridge University Press, 2025)
"Tracing the emergence of literary history, Alexander Jabbari shows how Iranians and South Asians drew from their shared literary heritage to produce a 'Persianate modernity' in the nineteenth and twentieth centuries. Using both Urdu and Persian-language sources, Jabbari examines how intellectual exchange across the region made national cultures"--
Histories : from Tazkirah to literary history -- Erotics : from bawdy to bashfulness -- Origin myths : indigeneity and hybridity in national narratives -- Print : typography, orthography, punctuation.
First publish 2023
Includes bibliographical references and index.
ENH
Keywords: Persian literature -- Iran -- History and criticism; Persian literature -- India -- History and criticism; Modernism (Literature) -- Iran; Modernism (Literature) -- India; Persian language -- Iran -- History; Persian language -- India -- History; Iran -- Relations -- India; India -- Relations -- Iran; Iran -- Intellectual life -- 19th century; India -- Intellectual life -- 19th century